Marketing virtual reality experiences … without the headset: watching, playing and fearing Anagram's Goliath. Issue 1 (2nd January 2022) - Freeman, Matthew
ABSTRACT: If the immersive sector is to capture new audiences from different corners of the cultural landscape, then gateway promotional content is needed – that is, marketing that engages those new to immersive technologies. Is it possible, however, to promote the unique pleasures that Virtual Reality (VR) offers without putting people in headsets? Exploring this question, this article outlines research that experiments with new ways of marketing VR experiences based on applying theoretical concepts to a marketing campaign for Goliath, a 2021 VR documentary produced by Anagram. The campaign tested out Baekdal's characterisation of two 'moments' of a VR experience: (1) a 'macro moment', which is experiencing VR yourself in a headset; and (2) a 'micro moment', which is presenting VR to people without a headset and whom prefer watching others in a VR environment rather participating in it themselves. This article argues that audiences new to VR are more likely to be engaged by promotion for VR if it presents a 'micro moment' of VR based on watching other people. We outline ways that the immersive sector can produce marketing for VR that better communicates not just what a VR experience is, but also what its audiences are expected to do.